Optimization of Vacuum Microwave-Mediated Extraction of Syringoside and Oleuropein from Twigs of Syringa oblata - Xiangping Liu; Xuemin Jing; Guoliang Li (Journal of Analytical Methods in Chemistry)
A vacuum microwave-mediated method was used to extract syringoside and oleuropein from Syringa oblata twigs. The optimal extraction conditions were an ethanol volume fraction of 40%, a liquid-solid ratio of 17 mL/g, 1 h of soaking time, −0.08 MPa of vacuum, a microwave irradiation power of 524 W, and a microwave irradiation time of 8 min. Under optimal parameters, the maximum yields of syringoside (5.92 ± 0.24 mg/g) and oleuropein (4.02 ± 0.18 mg/g) were obtained. The proposed method is more efficient than conventional methods for extracting syringoside and oleuropein from Syringa oblata. Moreover, less energy and time were required. The results implied that vacuum microwave-mediated extraction is a suitable method for the extraction of thermosensitive glycosides such as syringoside and oleuropein.